Peranan Hukum Perdata Nasional dalam Mengatur Para Pihak Bagi Pemerintah Daerah Provinsi dalam Kerja sama Funding untuk Proyek Non-APBN/APBD - Marsalina Susana; Urbanisasi Urbanisasi (Lembaga Pengembangan Kinerja Dosen, 2025)
The need for development financing in the regions is increasing, while dependence on the APBN/APBD funds cannot meet all those needs. Therefore, the regional government is starting to explore alternative financing cooperation, including with non-government entities (private and international financial institutions). This article aims to examine the role of national civil law as the legal basis for regulating the relationship between the parties in such cooperation schemes. This research uses a normative juridical method with an approach based on legislation and concepts. It is found that national civil law, particularly agreements in the Civil Code and modern contract law, plays a vital role in determining the rights and obligations of the parties, ensuring legal certainty, and preventing disputes in the implementation of non-APBN/APBD funding cooperation. In addition, the flexibility of civil law allows for adaptation to the needs of the region and funding partners. Strengthening the legal capacity of local governments and harmonizing with sectoral regulations are necessary.